Fungal chitosan as membranous material modified by atmospheric plasma (Research, Society and Development, 2021)
Objective: This study produced a fungal chitosan membrane extracted from Rhizopus stolonifer, as well as its modification using dielectric barrier discharge plasma (DBD), aiming to improve the physicochemical characteristics of the membrane, optimizing its use in the medical research field. Method: The obtained chitosan was physically and chemically characterized (Molecular Weight, Fourier Transform Infrared, X-ray Diffraction), later were produced fungal chitosan membranes and DBD plasma was applied. The membranes were characterized before and after plasma application using the tests contact angle, swelling and atomic force microscopy (medium roughness) analyzes. Results: A fungal chitosan with a yield of 16.73 mg/g, and an apparent molecular weight of 4 kDa was obtained, being considered of low molecular weight and high degree of deacetylation (84%). It was possible to obtain the membrane and after application of DBD plasma, the contact angle dropped from 77.5° to 30.9°, making it more hydrophilic. Conclusion: Thus, the efficiency of the technique for increasing the hydrophilicity of the fungal chitosan membrane without the additive of chemical reagents during the process was confirmed and the membrane formed is a promising alternative can be used in different ways in the medical area.